Pseudoephedrine and circadian rhythm interaction on neuromuscular performance - Pallares, J. G.; Lopez-Samanes, A.; Fernandez-Elias, V. E.; Aguado-Jimenez, R.; Ortega, J. F.; Gomez, C.; Ventura, R.; Segura, J.; Mora-Rodriguez, R. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study analyzed the effects of pseudoephedrine (PSE) provided at different time of day on neuromuscular performance, side effects, and violation of the current doping cut-off threshold [World Anti-Doping Agency (WADA)]. Nine resistance-trained males carried out bench press and full squat exercises against four incremental loads (25%, 50%, 75%, and 90% one repetition maximum [1RM]), in a randomized, double-blind, cross-over design. Participants ingested either 180 mg of PSE (supra-therapeutic dose) or placebo in the morning (7:00 h; AMPLAC and AMPSE) and in the afternoon (17:00 h; PMPLAC and PMPSE). PSE enhanced muscle contraction velocity against 25% and 50% 1RM loads, only when it was ingested in the mornings, and only in the full squat exercise (4.4-8.7%; P < 0.05). PSE ingestion raised urine and plasma PSE concentrations (P < 0.05) regardless of time of day; however, cathine only increased in the urine samples. PSE ingestion resulted in positive tests occurring in 11% of samples, and it rose some adverse side effects such us tachycardia and heart palpitations. Ingestion of a single dose of 180 mg of PSE results in enhanced lower body muscle contraction velocity against low and moderate loads only in the mornings. These mild performance improvements are accompanied by undesirable side effects and an 11% risk of surpassing the doping threshold.